Otherness In Miskin Al-Daramis Poetry - Ghazyah AL-Thobaiti (Journal of Umm Al-Qura University for Language Sciences and Literature, 2023)
The research aims to study otherness Miskin Al-Darami's poetry by interrogating the poetic text and monitoring the relationship between the poet's self and the harmonious otherness at one time and the oppositional one at another, and to demonstrate the effectiveness of otherness as a semantic engine for the poetic text in its various formal and content manifestations. The results concluded that otherness contributed positively to the poetic creativity of Miskin Al-Darami, who was distinguished by diversity and richness, in addition to its association with the environment and the religious, cultural and societal aspects with which harmonized with it and contributed to its enrichment.